Beclin-1 improves the cognitive function of mice with alzheimer"s disease - Li SHAO; Qing HE; Xin DU; Qing LI; Siyuan YANG; Chen DONG; Pengju MA (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2023)
We aimed to investigate the improvement effect of Beclin-1 on the cognitive function of mice with Alzheimer"s disease (AD). Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) were isolated from neonatal umbilical cord tissues. The cells stably overexpressing Beclin-1 were constructed, and those of passages 5, 10, and 15 were used. Forty-eight AD mice were randomly divided into AD, P5 hUC-MSCs, P15 hUC-MSCs (P15MSCs) and OE Beclin 1-P15 hUC-MSCs (OE Bec-P15MSCs) groups (n=12). Overexpressing Beclin-1 significantly enhanced the proliferation and migration of MSCs of different passages, and reduced G0/G1 arrest. The OE Bec-P15MSCs group had the longest total distance, the shortest time in forced swimming test, and the largest total food consumption in novelty suppressed feeding test. Transplanting hUC-MSCs and overexpressing Beclin-1 significantly reduced Aβ deposition. The expressions of P-tau (Ser396), P-tau (Ser231) and P-tau (Ser235) were significantly inhibited by hUC-MSCs transplantation and Beclin-1 overexpression, especially in the OE Bec- P15MSCs group. Double positive staining of EdU+/DCX+ cells, EdU+/NeuN+ cells and EdU+/Nestin+ cells significantly increased in the OE Bec-P15MSCs group compared to those in other groups (P<0.05). The activation degrees of astrocytes and microglia were lowest and the superoxide dismutase activity was highest in the OE Bec-P15MSCs group (P<0.05). The protein expression of nuclear factor E2-related factor 2 (Nrf2) in NAD(P) H quinone oxidoreductase 1 and superoxide dismutase 1 in brain tissues significantly rose, while that of Keap-1 was down-regulated in the OE Bec-P15MSCs group (P<0.05). Beclin-1 can partly restore the viability of hUC-MSCs by activating the Nrf2 signaling pathway, thereby enhancing the therapeutic effect of transplantation on AD mice.